Echocardiographic Predictors of Pulmonary Embolism in Patients Referred for Helical CT - Lodato, Joseph A.; Ward, R. Parker; Lang, Roberto M. (Echocardiography (Mount Kisco, N.Y.), 2008)
Background: Transthoracic echocardiography (TTE) is ordered frequently in patients with suspected pulmonary embolism (PE). Multiple indices have been suggested to play a useful diagnostic role. We sought to determine the relative predictive accuracy of suggested quantitative indices among patients referred for CT scanning for exclusion of PE. Methods: We retrospectively identified 67 consecutive patients who underwent CT for the exclusion of PE, and had a TTE within 48 hours of CT. Echo indices suggested to play a role in the diagnosis of PE were measured RV/LV area ratio, RV/LV end diastolic dimension ratio, the “McConnell” sign, interventricular septal shift (“D‐sign”), Pulmonary artery diameter, tricuspid regurgitation velocity, and “60/60 sign” (TR velocity < 3.9 m/sec plus pulmonary artery acceleration time < 60 msec). Results: CT confirmed PE in 41 (61%). Mean age was 58 (18–92). Forty‐five were female. Subjects with PE were younger, and more likely to be tachycardic and require ICU admission. Of the echocardiographic indices, RV/LV EDD ratio > 0.7 was the most accurate predictor (sensitivity 66%, specificity 77%). The McConnell sign was the most specific (96%), however, with poor sensitivity (16%). Mean TR velocities did not differ between those with and without PE (270 ± 74 vs. 294 ± 83, P = 0.25). Conclusions: RV/LV EDD ratio > 0.7 has good accuracy for the diagnosis of acute PE. RV/LV area ratio > 0.7 and McConnell sign are specific but not sensitive indicators of acute pulmonary embolism. The presence of these findings should prompt further diagnostic testing for PE.